Bacon and Shakspere - Burr, William Henry, 1819-1908 (Salt Lake City, UT : Project Gutenberg, 2012)
"Bacon and Shakspere" by William Henry Burr is a critical examination of the authorship of William Shakespeare's works, written as a polemic in the late 19th century. This publication includes the central argument that Shakespeare was incapable of writing the plays and poetry attributed to him, positing instead that Francis Bacon was the true author. Burr$1 (Bs book delves into the discrepancies in Shakespeare's signatures, the absence of any reliable likeness of him, and an analysis of the sonnets, alongside providing historical context to the Elizabethan era. In "Bacon and Shakspere," Burr meticulously scrutinizes various aspects of Shakespeare's life and work, ultimately claiming that the famous playwright was largely a front for Bacon's literary genius. He presents evidence such as the poor quality of Shakespeare's signatures, the lack of a definitive portrait of the playwright, and various legal documents to substantiate his argument that Shakespeare was illiterate. Additionally, Burr identifies Bacon as the (3z(Bconcealed poet Ignoto,(3y (Bsuggesting Bacon wrote not only the plays but also the sonnets falsely attributed to Shakespeare. The book asserts that Bacon$1 (Bs eloquence and intellect are far superior, arguing that his profound literary output has been obscured by the popular mythology surrounding Shakespeare. Ultimately, Burr$1 (Bs thesis challenges conventional literary history and invites readers to reconsider the authorship of literary masterpieces. (This is an automatically generated summary.)s
Release date is 2012-03-12
Produced by David Widger
Keywords: Shakespeare, William, 1564-1616 -- Authorship -- Baconian theory